Wittgenstein's Lectures on Religious Belief - Satris, Stephen (Philosophical investigations, 2014)
In this article, I want to do two things. The first is to conduct a sympathetic yet critical review of some of the salient features of the ideas in the notes that have come to us from Wittgenstein's Lectures on Religious Belief. This requires close reading, analysis and critique. The second, which comes out of the first, is to give some indication of Wittgenstein's failure to apply to his thinking about religious and moral matters some of the insights that he had already achieved as his philosophical thinking progressed.